KONTRIBUSI, EFEKTIVITAS, EFISIENSI, DAN FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN PAJAK PERTAMBAHAN NILAI - Mulyadi, M. Syarif (Jurnal Kajian Ekonomi dan Keuangan, 2011)
This paper examines the contribution, the effectiveness, and the efficiency of value added tax (VAT) revenue.lt also investigates the variables affecting the value added tax revenue. Using the ratio of VAT revenue to total government expenditures as the measurement of the contribution shows that VAT revenue contribution is 33 percent in average lower than income tax revenue contribution. Meanwhile the effectiveness of VAT is around 3,5 percent, still below the income tax effectiveness. In addition, the c-efficiency ratio is 0.50 in average which means that every 1 point increase in VAT tax rate results in an increase in VAT revenue by 0,50 percent of GDP. Furthermore, using ordinary least square estimation, the VAT revenue is determined by tax base, regulations, and the exemption policy where household and government consumption as tax base have positive and significant effect on VAT whereas previous import has a negative effect on VAT revenue.